Proceedings of the 1st ACM/IEEE International Conference on Cyber-Physical Systems 2010
DOI: 10.1145/1795194.1795218
|View full text |Cite
|
Sign up to set email alerts
|

A cyber-physical systems approach to energy management in data centers

Abstract: This paper presents a new control strategy for data centers that aims to optimize the trade-off between maximizing the payoff from the provided quality of computational services and minimizing energy costs for computation and cooling. The data center is modeled as two interacting dynamic networks: a computational (cyber) network representing the distribution and flow of computational tasks, and a thermal (physical) network characterizing the distribution and flow of thermal energy. To make the problem tractabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…We further study thermal-aware server and workload consolidation solutions to optimize the data centers' total energy consumption and ensure avoiding cooling computing power tradeoff. The existing thermal-aware scheduling algorithms for Internet data centers are heuristic in the sense that they are either based on simulation studies or do not provide guarantee on their optimality and avoiding cooling-computing power tradeoff [44,94,104].…”
Section: Application Of the Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further study thermal-aware server and workload consolidation solutions to optimize the data centers' total energy consumption and ensure avoiding cooling computing power tradeoff. The existing thermal-aware scheduling algorithms for Internet data centers are heuristic in the sense that they are either based on simulation studies or do not provide guarantee on their optimality and avoiding cooling-computing power tradeoff [44,94,104].…”
Section: Application Of the Solutionsmentioning
confidence: 99%
“…Sharma et al, introduced thermal load balancing and showed that dynamic thermal management based upon asymmetric workload placement can promote uniform temperature distribution and reduce cooling energy [104]. Parolini et al, provided analytical formulation to manage the workload distribution among servers which relies on the expected value of the traffic over time [94]. Thermal-aware server provisioning for IDCs is also studied by Faraz and Vijaykumar.…”
Section: Thermal-aware Schedulingmentioning
confidence: 99%
“…Tang et al [46] discuss a control algorithm that allocates the workload among servers so as to minimize their peak inlet temperatures. Parolini et al [47], [48] consider a data center as a node of the smartgrid, where time-varying and power-consumption-dependent electricity price information is used to manage data center operations.…”
Section: Data Center Level Controlmentioning
confidence: 99%
“…From an implementation viewpoint, the solution operates either locally (chip, server, etc.) [1], [14], [21] or globally (cluster, data center) [17], [10], [18], [19], [7], [16].…”
Section: Prior Workmentioning
confidence: 99%